El cooperativismo agrícola en el contexto de globalización. Un estudio exploratorio en el sur de Francia - Massera, Maricel Lorena (2020)
From an analysis of a cooperative and a cooperative group in the region of Lauragais in France, this paper aims to explore the consequences of globalization and capital concentration for agricultural cooperatives. We focus on cooperatives' internal organization, the links with their stakeholders and their strategies to adapt to change. We observe that both cases are crossed by the tension between achieving efficiency as collectively operated companies and the promotion of participation, democracy, and solidarity, showing a higher appreciation of the first objective with some slight differences.